1919 - (3CMeO eQGOs ((3GdbGgQI (B:s (3OGQ GdTQhb(B,s, 2014)
(3aj QhGjI (B1919(3, SjNWac CMeO eQGO aj BdI GdRef djgHW Hc aj MbHI JZdj ajgG GdbGgQI HGdCMOGK(B. (3hKHI RefjI Edi YGde eJTGHc jeSc ajg GdeDda ebJOQkG Hcd eaGJjMg, Hjf SYO RZdhd hJYfJ GdHQjWGfjjf, bUI GdhaO hebgi (B"(3eJGJjG(B"(3, LeGYI SQjI JYed JMJ ebgi (B"(3QjT(B"(3, hYGde GdHZGA Gdebff(B. (3TNUjGJ YOjOI Sha JJYJWa eYgG Ch JebJgG Ch JaYd GdTjFjf HdG JMaX, HMhGQ eaYe HGdMjhjI MJi JhTc Ydi SeGYg jJQOO aj CPfc, hJaGUjd JGQjNjI eVfjI hObjbI(B. (3Sha JOQc Cf GdHYV eGRGd eUQkG Ydi GdLOjI hGdEJbGf(B.s
Keywords: (3GdbUU GdYQHjIs -- (3eUQ(B.s; (3GdbUU GdJGQjNjI s -- (3eUQ(B.s